THE DESIGN OF READOUT FRONT-END ELECTRONICS FOR TIME AND ENERGY MEASUREMENTS FOR SEMICONDUCTOR STRIP DETECTORS - Kłeczek, Rafał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This work presents the design of the readout front-end electronics for time and energy measurements dedicated for double-sided strip detectors implemented in submicron technology UMC 180 nm CMOS. The simultaneous and accurate measurements of time and energy deposited in the detector by a photon requires the use of two different parallel processing paths in the single channel: fast and slow. The designed front-end electronics is characterized by low power dissipation level P=3.2 mW, low noise performance ENC=586 e- rms (for “slow” path and at Cdet=30 pF). The single channel occupies silicon chip area of 50 µm × 1100 µm.